Cryptographic Hardware and Embedded Systems - CHES 2008 - Oswald, Elisabeth (Springer, 2017)
This book constitutes the refereed proceedings of the 10th Interntaional Workshop on Cryptographic Hardware and Embedded Systems, CHES 2008, held in Washington, D.C., USA, during August 10-13, 2008. The book contains 2 invited talks and 27 revised full papers which were carefully reviewed and selected from 107 submissions. The papers are organized in topical sections on side channel analysis, implementations, fault analysis, random number generation, and cryptography and cryptanalysis.